Enigma of social media use: complexities of social media addiction through the serial mediating effects of emotions and self-presentation - Ho, Wing W. Y.; Lau, Yan H. Y.; Leung, Leona Y. L.; Li, Eric K. L.; Ma, Reyna K. K. (Frontiers in Psychology, 2024)
This study investigates the serial mediating effects of positive and negative affect, fear of missing out, and offline and online self-presentation in the relationship between social media use and social media addiction. The study was conducted in Hong Kong with 385 participants (84.2% F, age range = 18–60) of an online survey. The results indicate that social media use plays a significant role in predicting both positive and negative affect. The findings further reveal that positive and negative affect, fear of missing out, and offline and online self-presentation act as serial mediators in the relationship between social media use and social media addiction. In other words, these variables work together in a sequential manner to mediate the impact of social media use on addiction. Additionally, the study indicates that social media use and social media addiction are fully mediated by both positive and negative affect, fear of missing out, and offline and online self-presentation.